Intention, beliefs and mood assessed using electronic diaries predicts attendance at cardiac rehabilitation: An observational study. (December 2018) - Jones, Martyn C.; Smith, Karen; Herber, Oliver; White, Myra; Steele, Fiona; Johnston, Derek W.
Abstract: Background: Cardiac rehabilitationis effective in promoting physical/psychological recovery following acute coronary syndrome. Yet, rates of attendance at outpatient cardiac rehabilitation by eligible patients are low. Objectives: This study examined the determinants of attendance at outpatient cardiac rehabilitation in acute coronary syndrome patients following discharge until cardiac rehabilitation commencement. Design: A weekly electronic diary measured cardiac-related cognitions and mood and examined their relation to attendance at outpatient cardiac rehabilitation. Settings: Three United Kingdom National Health Service secondary care settings in two Health Board areas in Scotland. Participants: Acute coronary syndrome patients were recruited from March 2012 to June 2013 prior to hospital discharge. Of 488 eligible patients referred for cardiac rehabilitation, 214 consented. Methods: Consecutive patients completed a pre-hospital discharge questionnaire targeting age, diagnosis, social class and smoking history. Acute coronary syndrome patients then completed a weekly electronic diary from the first week of discharge until the start of cardiac rehabilitation. Multilevel structural equation models estimated the effects of initial, i.e. baseline and rate of change in cardiac-related cognition and mood on attendance. Intention to attend cardiac rehabilitation was reflected, log transformed, reported thereafter as "do not intend". The role of "do not intend" was explored as a mediator of the relationship between cardiac-related cognition and mood on attendance. Results: 166 participants provided, on average, 5 weeks of diary entries before cardiac rehabilitation commenced. High intention (i.e. low "do not intend") to attend CR and its rate of increase over time predicted attendance. Low negative emotional representation, high perceived necessity, high confidence in maintaining function, low negative affect, and high positive affect following discharge predicted attendance at cardiac rehabilitation. The rate of change in cardiac-related mood and these cognitions was not predictive. Baseline and rate of change in "do not intend" entirely mediated relationships between a) perceived necessity, b) negative affect and attendance at cardiac rehabilitation. Conclusions: Negative affect in the first weeks following discharge represents the key challenge to a patient maintaining their intention to attend cardiac rehabilitation. Intervention to improve attendance should focus on improving intention to attend following discharge and during recovery by improving patient understanding of cardiac rehabilitation and reducing negative affect.